Can someone please help me with this ?
Use iteration method to solve it. T(n) = T(n-1) +n
Explanation of steps would be greatly appreciated.
Iteration Method. The iteration method is a "brute force" method of solving a recurrence relation. The general idea is to iteratively substitute the value of the recurrent part of the equation until a pattern (usually a summation) is noticed, at which point the summation can be used to evaluate the recurrence.
It is O(n^2) .
this is a Geometric series with log(n) terms and each term gets halved. Hence answer is O(N).
T(n) = T(n-1) + n
T(n-1) = T(n-2) + n-1
T(n-2) = T(n-3) + n-2
and so on you can substitute the value of T(n-1) and T(n-2) in T(n) to get a general idea of the pattern.
T(n) = T(n-2) + n-1 + n
T(n) = T(n-3) + n-2 + n-1 + n
.
.
.
T(n) = T(n-k) + kn - k(k-1)/2 ...(1)
For base case:
n - k = 1 so we can get T(1)
=> k = n - 1
substitute in (1)
T(n) = T(1) + (n-1)n - (n-1)(n-2)/2
Which you can see is of Order n2 => O(n2).
Expand it!
T(n) = T(n-1) + n = T(n-2) + (n-1) + n = T(n-3) + (n-2) + (n-1) + n
and so on, until
T(n) = 1 + 2 + ... + n = n(n+1)/2 [= O(n^2)]
provided that T(1) = 1
If you love us? You can donate to us via Paypal or buy me a coffee so we can maintain and grow! Thank you!
Donate Us With